Between disputes and negotiations: the historical construction of the cocoa region from the newspaper Gazeta de Ilhéos (1901-1904) - Souza, Gabriel José Brandão de (Revista Crítica Histórica, 2020)
This article aims to analyze the process of constructing the historical narrative of the cocoa region from political and ideological disputes between the elite groups of the city of Ilhéus-BA in the early twentieth century. For a better understanding of this dispute process, use as a main source the newspaper change and permanence. In this sense, we are interested in how these groups use the press not only as a diffuser of ideas and ideals, but also as an important political objective of opposition. of their opinions and dispute of spaces of power. Therefore, understand a discursive strategy linked in this press, despite the attempt to construct a speech of impartiality.